RETRACTED ARTICLE: Significance of the IL-8 pathway for immunotherapy - Manuela Gonzalez-Aparicio; Carlos Alfaro (Taylor & Francis Group, 2020)
We, the Publisher of Human Vaccines & Immunotherapeutics, have retracted the following article: Manuela Gonzalez-Aparicio and Carlos Alfaro, "Significance of the IL-8 pathway for immunotherapy," Human Vaccines & Immunotherapeutics, volume 16, issue 10, 2312-2317, doi: 10.1080/21645515.2019.1696075 This article has been retracted because it contains an unacceptable level of text overlap with previously published sources: [1]           D. J. J. Waugh and C. Wilson, "The interleukin-8 pathway in cancer," Clin Cancer Res, vol. 14, pp. 6735-41, Nov 1 2008. [2]           B. S. Qazi, K. Tang, and A. Qazi, "Recent Advances in Underlying Pathologies Provide Insight into Interleukin-8 Expression-Mediated Inflammation and Angiogenesis," International Journal of Inflammation, vol. 2011, pp. 1-13, 2011. [3]           Q. Liu, A. Li, Y. Tiana, J. D. Wuc, Y. Liud, T. Lib, et al., "The CXCL8-CXCR1/2 pathways in cancer," Cytokine Growth Factor Review, pp. 61-71, 2016. [4]           N. Vij, A. Sharma, M. Thakkar, S. Sinha, and R. R. Mohan, "PDGF-driven proliferation, migration, and IL8 chemokine secretion in human corneal fibroblasts involve JAK2-STAT3 signaling pathway," Molecular Vision, pp. 1020-1027, 2008. [5]           I. M. Bermejo, E. M. Jaffee, D. Davar, J. Cardarelli, D. Williams, P. Phillips, et al., "Phase 1b/2 study of nivolumab in combination with an anti-IL-8 monoclonal antibody, BMS-986253, in a biomarker-enriched population of patients with advanced cancer," vol. 36, pp. TPS3109-TPS3109, 2018. The authors did not provide adequate indication of the source material and in their initial response were unable to provide satisfactory details regarding copyright clearance to reproduce the published material.  Author Manuela Gonzalez-Aparicio did not respond, and author Carlos Alfaro Alegría agreed with the decision to retract this article. We have been informed in our decision-making by our policy on publishing ethics and integrity and the COPE guidelines on retractions. The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as "Retracted."